Exploring the Role of Information Communication Technology and Renewable Energy in Environmental Quality of South-East Asian Emerging Economies - Zeeshan, Muhammad; Han, Jiabin; Rehman, Alam; Ullah, Irfan; Mubashir, Muhammad (Frontiers in Environmental Science, 2022)
We extend the literature on ICT and renewable energy relationship with environmental quality to Southeast Asian region, as prior literature is mostly focused on a single country case, and to investigate the regional panel, especially Southeast Asian region is one of the gap in the existing body of knowledge. The deliberation of ICT and renewable energy use are among the top priorities of each economy in this region. We peruse this study with the intention to diagnose the pattern of practices of these countries towards ICT and Renewable energy, and how these emerging factors contribute to the environmental performance. We analyze the annual data of six countries for the period 2000 to 2018, using Panel Quantile Regression, and Dynamic Fixed Effect estimation techniques to test the hypothesized short run as well as long run relationship of ICT and renewable energy with environmental quality. Our empirical results reveal the non-mitigating effect of ICT in CO2 emission, confirming that ICT in this region does not improve environmental performance, rather cause more environmental degradation in the region. While renewable energy demonstrates significant contribution to environmental quality in this region. Our results are coherent with many studies in the existing body of knowledge. The findings are very meaningful and handy for the policy makers in these selected countries to frame strategies in term of renewable energy and ICT practices of such nature that could favor the environment.